Utility of point-of-care testing of natriuretic peptides (brain natriuretic peptide and n-terminal pro-brain natriuretic peptide) in the emergency department - Nayer, Jamshed (Medknow Publications & Media Pvt Ltd, 2014)
Rapid and accurate diagnosis of a patient with an acute disease is a challenge for emergency physicians. Natriuretic peptides have emerged as important tools for diagnosis, risk stratification and therapeutic decision making for some categories of emergency patients. Brain natriuretic peptide (BNP) is a member of a four natriuretic peptides family that shares a common 17-peptide ring structure. Atrial natriuretic peptide, C-natriuretic peptide (CNP), and D-type natriuretic peptide are the other natriuretic peptide, which share the same common 17-peptide ring structure. The N-terminal fragment of pro-BNP, N-terminal pro-brain natriuretic peptide (NT-proBNP) consists of 76 amino acids, which is biologically inert, while the active component BNP contains 32 amino acids. BNP and NT-proBNP are secreted in the plasma in equimolar quantities and are frequently used in the diagnosis of congestive heart failure, and distinguishing between patients with dyspnea of cardiac or pulmonary origin. Both natriuretic peptides have also been evaluated for use in the assessment and management of several other conditions including sepsis, cirrhosis of liver and renal failure. However, one should remember that the values of natriuretic peptides are affected by age and weight of the patients, and presence of several comorbidities such as chronic renal failure, type 2 diabetes mellitus, anemia, pulmonary embolism, and acute coronary syndrome. Values of these peptides also vary depending on the type of test used. The performance characteristics of these natriuretic peptides vary depending on the patients on whom they are used. Therefore determination of reference values for these peptides represents a challenge.